Peran Stakeholders dalam Pemberdayaan Kelompok Budidaya Ikan (POKDAKAN) di Kecamatan Kuranji - Wizi, Dhea Apprilia; Eriyanti, Fitri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The research purpose to understand the role of stakeholders in empowering fish farming groups (Pokdakan) in Kuranji Subdistrict and the inhibiting factors in this empowerment. The researcher employs a qualitative research approach throught a method in descriptive. The informants for research were got using techniques of purposive sampling. The methods for data collection include interviews, observations, and document studies. The data validity was verified through triangulation, and the data analysis process involved reduction of data, presentation of data, and ,making conclusions. The research results shown that stakeholders act as policy creators, coordinators, facilitators, implementers, and accelerators. However, the empowerment of Pokdakan in Kuranji Subdistrict has not yet been fully optimized. The inhibiting factors in implementing empowerment include budget constraints, lengthy and complicated administrative processes, limited human resources, and the limited time available to stakeholders.